Smart governance warunkiem osiągnięcia neutralności klimatycznej - Pinkas, Aleksandra (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2021)
The ongoing energy transition aimed at achieving by European Union climate neutrality to 2050 year requires public participation. The need to develop a new climate-energy strategy is an obligation under European climate law. This requires Member States to take effective measures in the long term, which will be adapted to national capabilities. Smart governance as a model of social participation in the process of co-governance is a condition to introduce a zero-emission economy, where economic growth is separated from the negative impact on the environment
Keywords: Energy law; European climate law; climate neutrality; smart governance; social participation